Investigation Of The Psychological Effects Of Social Media Use Among Students In Minnesota, United State America - Toyosi Motilola Olola; Akpan Ubong-Abasi Asukwo; Funmilayo Odufuwa (Britain International for Academic Research (BIAR) Publisher, 2023)
The study looked into the psychological effects of social media use among students in Minnesota, USA. Specifically, the study assessed the various psychological effects of social media on students in Minnesota and the United States of America. It investigated the impact of social media use on the psychological well-being of students in Minnesota, United States of America. The study adopted a descriptive survey research design. The sample for the study consisted of two hundred (200) students that were randomly selected using a simple random sampling technique. One research instrument tagged